2019
DOI: 10.1002/est2.50
|View full text |Cite
|
Sign up to set email alerts
|

On the integration of the energy storage in smart grids: Technologies and applications

Abstract: Smart grids are one of the major challenges of the energy sector for both the energy demand and energy supply in smart communities and cities. Grid connected energy storage systems are regarded as promising solutions for providing ancillary services to electricity networks and to play an important role in the development of smart grids. The aim of the present article is to analyze the role of storage systems in the development of smart grids. The article includes an analysis and a list of energy storage system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 98 publications
(159 reference statements)
0
18
0
2
Order By: Relevance
“…The electricity production is promoted through the integration of photovoltaic modules on the buildings to cover the energy demand during most of the year considering also the use of energy storage systems [71] with light green mobility [72] as transition to Zero Energy Emission Districts (ZEED) [73]. The roofing systems are conceived to install surfaces for renewable energy exploitation optimizing the slope and configuration and the settlement design.…”
Section: Nearly Zero Energy Building Concept In Povegliamentioning
confidence: 99%
“…The electricity production is promoted through the integration of photovoltaic modules on the buildings to cover the energy demand during most of the year considering also the use of energy storage systems [71] with light green mobility [72] as transition to Zero Energy Emission Districts (ZEED) [73]. The roofing systems are conceived to install surfaces for renewable energy exploitation optimizing the slope and configuration and the settlement design.…”
Section: Nearly Zero Energy Building Concept In Povegliamentioning
confidence: 99%
“…Due to the main concerns of Li‐ion batteries usage such as the overall cost, the limited number of charging cycles or lifetime, the depth of discharge, the relatively low energy density, and the sustainability of the materials used, it is suggested to consider flow batteries as a better alternative in future work. Moreover, considering the economical and safety aspect of hydrogen storage, several researchers became interested toward its solid‐state storage through adsorption and/or absorption on materials/alloys, it is suggested to consider solid‐state hydrogen storage or better ammonia storage scenarios in future work to improve the efficiency of the overall system.…”
Section: Future Workmentioning
confidence: 99%
“…Among the various types of battery technologies available, the two major types are nickel metal hydride (NiMH) and lithium‐ion (Li‐ion), however, the adoption of Li‐ion batteries is taking over since NiMH technology has reached maturity stage while Li‐ion technology has great potential for further advanced improvements . On the other hand, there are also flow batteries which are under intensive research, as a better alternative for larger‐scale storage . Although battery technology has improved dramatically during recent years, further improvement is needed to increase the energy density and to reduce the cost to make them more viable .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this technology is a relatively large-scale energy storage type with high reliability, long service life, low construction cost, acceptable performance, and an environmental friendly one. 3 Only two commercial-scale cavern-based CAES plants have been constructed to date: a 290 MW facility in Huntorf, Germany in 1978, and a 110 MW facility in McIntosh, USA in 1991. 4 Across the world, there are some other CAES plants in operation, under construction or being explored.…”
Section: Introductionmentioning
confidence: 99%
“…Cavern‐based compressed air energy storage (CAES) technology is a type of energy storage that stores surplus energy of the grid in the form of high pressure compressed air in a cavern. It has been shown that this technology is a relatively large‐scale energy storage type with high reliability, long service life, low construction cost, acceptable performance, and an environmental friendly one 3 …”
Section: Introductionmentioning
confidence: 99%